Complications of Teeth Affected by Molar-Incisor Malformation and Pathogenesis According to Microbiome Analysis - Hyo-Seol Lee; Hee Jin Kim; Koeun Lee; Mi Sun Kim; Ok Hyung Nam; Sung-Chul Choi (Applied Sciences, 2020)
A molar-incisor malformation (MIM) is a recently reported dental anomaly that causes premature loss of the first molar with severe dentoalveolar infection. However, there has been no research on the pathogenesis yet. The aim of this study was to report the clinical process of MIMs and investigate the pathogenesis by conducting a microbiome analysis. An eight-year-old girl was diagnosed with MIM and after two years, four permanent first molars were sequentially extracted due to severe dentoalveolar infection. We recorded the patient`s clinical progress and collected oral microbiome samples from the extracted teeth with MIM and sound teeth as controls. The sites of microbiome sampling were represented by five habitats in two groups. Group (1) was the perio group: ① supragingival plaque, ② subgingival plaque, and ③ a pical abscess; and group (2) was the endo group: ④ coronal pulp chamber and ⑤ root canal. The perio group was composed predominantly of genera Streptococcus, Veilonella, and Leptotrichia. Spirochetes appeared in one sample from a severe periodontal abscess. Aggregatibacter actinomyces were not identified. In the endo groups, pulp necrosis was observed in all MIM and the genera Peptostreptococcus and Parvimonas predominated. In conclusion, MIM teeth caused localized tooth-related periodontitis with pulp necrosis rather than localized juvenile periodontitis, resulting in a poor prognosis, and timely extraction is highly recommended.